1941
DOI: 10.1084/jem.74.6.621
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by Phospholipids of the Action of Synthetic Detergents on Bacteria

Abstract: Certain of the synthetic detergents exert a marked inhibitory effect on the metabolism (1) and viability (2) of bacteria. The germicidal action of these compounds and other biological effects have been studied by numerous investigators. 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

1943
1943
1972
1972

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(23 citation statements)
references
References 14 publications
(8 reference statements)
2
21
0
Order By: Relevance
“…The experiments presented above are, to our knowledge, the first ones to indicate the reversibility of the antibacterial ("killing") effect of surface active cations. Baker, Harrison and Miller (1941) recently attempted reversal with phospholipids which, as they demonstrated inhibit the antibacterial effect of surface active cations when simultaneously applied to the bacteria. Their results were negative, possibly because the time of exposure of the bacteria to the toxic cation, 30 minutes, was too long or because the phospholipids are not powerful enough detoxicating agents.…”
Section: Discussionmentioning
confidence: 99%
“…The experiments presented above are, to our knowledge, the first ones to indicate the reversibility of the antibacterial ("killing") effect of surface active cations. Baker, Harrison and Miller (1941) recently attempted reversal with phospholipids which, as they demonstrated inhibit the antibacterial effect of surface active cations when simultaneously applied to the bacteria. Their results were negative, possibly because the time of exposure of the bacteria to the toxic cation, 30 minutes, was too long or because the phospholipids are not powerful enough detoxicating agents.…”
Section: Discussionmentioning
confidence: 99%
“…Autolysis of bacteria associated with treatment of cells in low and high concentrations of surface-active agents has been well established in previous studies. This phenomenon was reviewed by Dubos (1945), and Hotchkiss (1946) has contributed further information. The possibility of physical solubilization of cellular materials in bacteria + detergent studies has been suggested by the work of Stacey (1949).…”
Section: R J Saltonmentioning
confidence: 99%
“…Phosphatides of the lecithin type interfere with the antibacterial action of polymyxin (Bliss et al 1949), and in this respect polymyxin exhibits properties similar to those of the cationic detergents (Baker, Harrison & Miller, 1941). Rybak (1950) showed that insoluble complex formation takes place between polymyxin and serum albumin; a similar action also occurs with yeast ribonucleic acid (Latterade & Macheboeuf, 1950).…”
mentioning
confidence: 99%